Keeping track of expert teachers: Comparing the affordances of think-aloud elicited by two different video perspectives. (August 2022) - McIntyre, Nora A.; Draycott, Beth; Wolff, Charlotte E.
Abstract: Verbal data from think-aloud is uniquely unobtrusive and non-reactive. It can therefore generate real-time insight into how expert teachers think. Our paper analyses data from two video-stimulated retrospective think-aloud approaches. The first approach used videos of others' teaching as stimuli for participating teachers' think-aloud. The second approach involved the teachers' own-perspective videos, overlaid with the teachers' own gaze patterns that were simultaneously recorded. In all, the study sets out to investigate how these two approaches differ with regard to their respective potential for uncovering expert teacher cognition. Others' videos elicited more think-aloud responses than gaze-cued own-perspective videos, especially the operational aspects of classroom teaching . Interaction analysis revealed expert–novice differences to vanish when only think-aloud responses to gaze-cued own-perspective videos were considered. Classroom relationships might be integral for any teacher's navigation of classroom instruction, regardless of expertise. Highlights: Others' videos prompted more think-aloud than gaze-cued own-perspective videos. In particular, others' videos elicited about operational aspects of teaching . Expertise differences disappeared during gaze-cued own-perspective think-aloud. Relationships seem integral to classroom instruction, regardless of expertise.